Altered states of consciousness. - Greenfield, Susan (Social Research)
Part of a special issue on altered states of consciousness. The writer discusses how the physical characteristics of people's brains are related to consciousness. She contends that the unique property in the brain that generates consciousness has a lot to do with feelings. Furthermore, she argues that the critical factor in determining the physical basis of consciousness is not qualitative but quantitative: The bigger the assembly of brain cells, the greater the depth of consciousness.